Justiça e o paradigma da eficácia: uma construção teleológica aplicada aos campos sociais em Pierre Bourdieu - Raimundo, Renato Martins (2019)
The present work aims to criticize the idea of "efficiency of justice" and propose a new paradigm in function of a teleology of the Judiciary. From the construction of this teleology, the paradigm of effectiveness is proposed as the best way to act, considering that the only efficient conduct is not able to pacify society, or even reduce the number of processes that enter the justice system each year. Uncovering processes of domination that exist behind the goals of judgment imposed by the National Council of Justice, the present work draws on the teachings of Greek philosophy to build a teleology proper to the Judiciary; and by relating the ideas of efficiency and effectiveness with the philosophies of Machiavelli and John Stuart Mill, it discovers the best way of acting for the Judiciary in function of its teleology. With the concepts of the social field present in Pierre Bourdieu's doctrine, it is possible to investigate the reasons why efficiency is used as a control instrument, which benefits the dominant in the field to the detriment of society, a real destination for the effects of judicial decisions. The research methodology used is the dialectic, through the confrontation of antagonistic ideas for the reconstruction of the interpretation of reality. In this sense, works of dominant authors of several schools of thought are used, as well as scientific articles related to the subject under discussion. In this way, the proposal aims at a bibliographical revision on the subject, proposing a reflection on the important question.